KOMODIFIKASI WISATA SPIRITUAL DI PUJA MANDALA NUSA DUA BALI - Ni Desak Made Santi Diwyarthi (Pusat penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2010)
Spiritual tourism has made some places of homage undergo comodification; a process in which the object, quality, activities, space and the spiritual activities are treated as commodity to satisfy the market needs. This writing describes how the process takes place in the protestant church in Puja Mandala Nusa Dua Bali. The church was not initially built or meeting the tourism market needs and the activities conducted in the Church are not products of arts which are specially created for commercial purposes. However, the Church experiences com modification process and becomes a place of spiritual tourism. It means that both the building of the church and its services are also aimed at meeting the tourism market needs. This indicates the relevance between spiritual values and modernity which is shifted into commercial relationship. The capitalist interest makes use the Church as a commodity that has selling values.